Failure Mechanism for Fast‐Charged Lithium Metal Batteries with Liquid Electrolytes. Issue 3 (11th September 2014) - Lv, Dongping; Shao, Yuyan; Lozano, Terence; Bennett, Wendy D.; Graff, Gordon L.; Polzin, Bryant; Zhang, Jiguang; Engelhard, Mark H.; Saenz, Natalio T.; Henderson, Wesley A.; Bhattacharya, Priyanka; Liu, Jun; et al.
<x xml:space="preserve">Abstract</x> In recent years, the Li metal anode has regained a position of paramount research interest because of the necessity for employing Li metal in next‐generation battery technologies such as Li‐S and Li‐O2. Severely limiting this utilization, however, are the rapid capacity degradation and safety issues associated with rechargeable Li metal anodes. A fundamental understanding of the failure mechanism of Li metal at high charge rates has remained elusive due to the complicated interfacial chemistry that occurs between Li metal and liquid electrolytes. Here, it is demonstrated that at high current density the quick formation of a highly resistive solid electrolyte interphase (SEI) entangled with Li metal, which grows towards the bulk Li, dramatically increases up the cell impedance and this is the actual origin of the onset of cell degradation and failure. This is instead of dendritic or mossy Li growing outwards from the metal surface towards/through the separator and/or the consumption of the Li and electrolyte through side reactions. Interphase, in this context, refers to a substantive layer rather than a thin interfacial layer. Discerning the mechanisms and consequences for this interphase formation is crucial for resolving the stability and safety issues associated with Li metal anodes.